2014
DOI: 10.1001/jamainternmed.2014.4649
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Defensive Medicine on 3 Hospital Medicine Services

Abstract: participated in data collection and did not receive compensation for their roles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 1 publication
2
57
0
3
Order By: Relevance
“…Our results are consistent with other studies that assessed the cost of DM on the healthcare system budget, both on the aggregate and patient levels [5,10,13,19,20]. This means that the practice of DM could represent one of the major causes of the budget deficit of the Italian National Health Service over recent years.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results are consistent with other studies that assessed the cost of DM on the healthcare system budget, both on the aggregate and patient levels [5,10,13,19,20]. This means that the practice of DM could represent one of the major causes of the budget deficit of the Italian National Health Service over recent years.…”
Section: Discussionsupporting
confidence: 91%
“…This result is consistent with the results of similar studies in other countries and with literature that suggests how medical malpractice reforms would reduce the costs of DM and litigation [5,7,13,24,30,31]. Recent papers argued that physicians" attitudes about DM do not correlate with legal risk and criticised the possible effect of tort reform [20,25]. We believe that tort reform is necessary, even though unlikely sufficient to eliminate the practice of DM, since half of the interviewed physicians did not mention it as the best system strategy [32].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The survey became part of the Cleveland Clinic study and showed that 28% of 4,200 orders were estimated as partially defensive, and 2.9% as completely defensive [17].…”
Section: Defensive Medicine In Various Countriesmentioning
confidence: 99%